2021
DOI: 10.1111/exd.14266
|View full text |Cite
|
Sign up to set email alerts
|

Molecular effects of photon irradiation and subsequent aftercare treatment with dexpanthenol‐containing ointment or liquid in 3D models of human skin and non‐keratinized oral mucosa

Abstract: This study aimed to investigate the molecular effects of radiation and subsequent aftercare treatment with dexpanthenol‐containing ointment and liquid on established full‐thickness 3D skin models depicting acute radiodermatitis and mucositis. To mimic radiomucositis and radiodermatitis, non‐keratinized mucous membrane and normal human skin models were irradiated with 5 Gray. Afterwards, models were treated topically every second day with dexpanthenol‐containing ointment or liquid in comparison with placebo and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Similar results were found with a reduction of postoperative pain and signs of inflammation in a randomized and placebo-controlled clinical trial [22]. Another in vitro study showed that a dexpanthenol-containing ointment had a favorable impact on structures critical to antimicrobial barrier function and had anti-inflammatory effects after photon irradiation [23].…”
Section: Introductionsupporting
confidence: 69%
“…Similar results were found with a reduction of postoperative pain and signs of inflammation in a randomized and placebo-controlled clinical trial [22]. Another in vitro study showed that a dexpanthenol-containing ointment had a favorable impact on structures critical to antimicrobial barrier function and had anti-inflammatory effects after photon irradiation [23].…”
Section: Introductionsupporting
confidence: 69%
“…Thus, it is conceivable that macrophage activation is greater with PLLA‐SCA than CaHA‐CMC and may explain differences in mechanism of action, with PLLA‐SCA having an immune‐mediated regenerative effect driven primarily by M2 macrophage polarization and CaHA‐CMC having a mechanotransductive effect independent of robust inflammation 4,33 . This hypothesis is supported by a recent gene expression study that showed PLLA‐SCA's mechanism of action largely functioned through the upregulation of inflammasomes IL1‐α, IL1‐β, and CXCL6, which contributed to dermal thickening and neocollagenesis, 16 a study showing macrophage‐dependent neocollagenesis with PLLA‐SCA 11 , and studies showing contact‐dependent neocollagenesis with CaHA‐CMC 4 . The body's ability to recognize size discrepancies in foreign objects underscores the importance of understanding and optimizing particle morphology to minimize adverse immune reactions and enhance therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 94%
“…showed that PLLA particles were encapsulated rather by the less organized collagen type III than type I 14 . Data suggests that the mechanism of action of PLLA relies on the involvement of the immune system for neocollagenesis, a distinctly different mechanism of action compared to CaHA‐CMC 11,15,16 . Previous studies indicate the particles that compose PLLA are heterogeneous and resemble flakes, rather than smooth microspheres 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schmutz et al reported non-inferiority in maintaining TEWL scores in acute radiation dermatitis (0.1% methylprednisolone cream vs. 0.5% dexpanthenol cream) [ 75 ]. As shown in full-thickness 3D skin models representing acute radiodermatitis and mucositis, skin impairment seven days after radiotherapy demonstrated a completely restored epidermal part after treatment with dexpanthenol-containing ointment or liquid [ 76 ].…”
Section: How Dexpanthenol Can Help In Admentioning
confidence: 99%